A kind of anticorrosive coating with self-repairing function and preparation method thereof

By using the combination of phosphor components and self-healing components in self-healing coatings, the problem of catalyst dependence and long self-healing time is solved by using the complex catalytic action of rare earth phosphors and imidazole N-heterocyclic carbene in the self-healing coatings. , achieves rapid self-healing and powerful self-healing effects.

CN118652590BActive Publication Date: 2024-12-20JIANGSU CHAMPION TECHNOLOGY GROUP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410895156.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-04
Publication Date
2024-12-20
Estimated Expiration
2044-07-04

AI Technical Summary

Technical Problem

The existing catalyst-type self-repair coatings require the outside world to provide catalyst when the coating is damaged, resulting in a long self-repair time and incomplete function.

Method used

Using the combination of phosphor components and self-healing components, the rare earth phosphor in the phosphor components forms a complex with imidazole N-heterocyclic carbene under sunlight, which serves as a catalyst to accelerate the self-healing process and shorten the self-healing process. Repair time and improve self-healing functions.

Benefits of technology

It realizes automatic start-up and rapid response of the catalyst, significantly shortening the self-repair time, and enhancing the perfection and speed of the self-repair function.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118652590B_ABST
    Figure CN118652590B_ABST
Patent Text Reader

Abstract

The present application relates to the field of coating technology, and specifically discloses a self-repairing anticorrosion coating and a preparation method thereof, a self-repairing anticorrosion coating, including a phosphor component and a self-healing component; the self-healing component includes the following raw materials in parts by weight: 20-50 parts of imidazole N-heterocyclic carbene, 50-90 parts of self-healing gel and 40-90 parts of self-healing toughening material; the preparation method of the self-repairing anticorrosion coating: the self-healing gel, the self-healing toughening material and the imidazole N-heterocyclic carbene are mixed and stirred to obtain the self-healing component. The self-repairing anticorrosion coating of the present application has a catalyst that responds instantly when the anticorrosion coating is damaged, and automatically starts the catalytic function, accelerates the self-healing process of the self-healing component, shortens the self-repairing time of the anticorrosion coating with the self-repairing function, and improves the advantages of the self-repairing function of the anticorrosion coating with the self-repairing function.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of coatings, and more specifically, to an anti-corrosion coating with self-repairing function and a preparation method thereof. Background Art

[0002] Paint is indispensable in many fields such as construction, aerospace, transportation, electronics, sports and military supplies. However, paint is also very easy to be scratched, causing the scratched substrate to be exposed to the air for a long time and begin to rust and deteriorate. Therefore, researchers are committed to developing a paint with self-healing function.

[0003] Existing self-healing coatings usually include the following key technical components: microencapsulation technology, in which the coating contains tiny capsules that release repair agents when the coating is damaged; nanocomposites, which improve the mechanical strength and wear resistance of the coating; smart polymers, which can undergo physical or chemical changes under specific conditions to achieve repair; catalysts, which are used to accelerate the repair process; auxiliary additives, such as UV-resistant and water-resistant molecules, which enhance the performance of the coating.

[0004] However, the existing catalyst-based self-repairing coatings can only accelerate the self-repair process after the coating is damaged through the provision of catalysts from the outside, which has the disadvantages of long self-repairing time and imperfect self-repairing function. Summary of the invention

[0005] In order to solve the shortcomings of the above-mentioned catalyst-based self-repairing coatings, such as long self-repairing time and imperfect self-repairing function, the present application provides an anti-corrosion coating with self-repairing function and a preparation method thereof.

[0006] The present application provides an anti-corrosion coating with self-repairing function and a preparation method thereof, which adopts the following technical scheme:

[0007] In the first aspect, the present application provides an anti-corrosion coating with a self-repairing function, comprising a fluorescent powder component and a self-healing component; the fluorescent powder component comprises the following raw materials in parts by weight: 20-30 parts of rare earth fluorescent powder, 5-8 parts of nano-adhesive and 30-50 parts of n-hexane, and the nano-adhesive is coated with the rare earth fluorescent powder; the self-healing component comprises the following raw materials in parts by weight: 20-50 parts of imidazole N-heterocyclic carbene, 50-90 parts of self-healing gel and 40-90 parts of self-healing toughening material.

[0008] By adopting the above technical scheme, when the two components constituting the self-healing coating are jointly coated on the substrate, both can play their respective functions. The phosphor component is one of the catalyst raw materials of the self-healing component. When the self-healing component is scratched, the phosphor component is exposed. Under the irradiation of sunlight, the substance in the phosphor component can form a complex with the imidazole N-heterocyclic carbene. The complex can act as a catalyst to accelerate the self-healing process of the self-healing component which has self-healing ability. When the anti-corrosion coating of the present application is damaged, the catalyst in the self-healing anti-corrosion coating responds instantly and automatically starts the catalytic function, thereby accelerating the self-healing process of the self-healing component, shortening the self-repair time of the anti-corrosion coating with self-repairing function, and improving the self-repair function of the anti-corrosion coating with self-repairing function.

[0009] The self-healing gel in the self-healing component is the part that has self-healing ability itself; the self-healing toughening material in the self-healing component is the part that has both self-healing function and toughening and strengthening function. Therefore, the self-repairing anti-corrosion coating composed of the self-healing gel and the self-healing toughening material itself has the functions of self-healing and strengthening and toughening.

[0010] Optionally, based on the self-healing gel, the self-healing gel includes the following raw materials in parts by weight: 10-20 parts of polyvinyl alcohol, 15-20 parts of 3-methyl-15-glutaraldehyde, 5-8 parts of sodium bicarbonate and 20-40 parts of methanol.

[0011] By adopting the above technical scheme, polyvinyl alcohol is a highly polymerizable substance. When polyvinyl alcohol is mixed with 3-methyl-15-glutaraldehyde, polyvinyl alcohol can not only undergo self-polymerization, but also undergo hydroxyaldehyde condensation with 3-methyl-15-glutaraldehyde under the catalysis of sodium bicarbonate, thereby further accelerating the self-healing function of the self-healing gel material; the self-healing function of the anti-corrosion coating with self-healing function finally obtained is stronger and faster.

[0012] Optionally, based on the self-healing toughening material, the self-healing toughening material includes the following raw materials in parts by weight: 10-15 parts of cellulose, 10-20 parts of glutaraldehyde, 4-7 parts of sodium hydroxide and 20-45 parts of N,N-dimethylformamide.

[0013] By adopting the above technical scheme, cellulose is a network structure material with self-polymerization function, which can enhance the strength and toughness of the self-healing toughening material. When cellulose is mixed with glutaraldehyde, under the catalysis of sodium hydroxide, cellulose can undergo an aldol condensation reaction with glutaraldehyde, so that the cellulose with a network structure can further enhance the strength of the network structure through the connection of glutaraldehyde, and further accelerate the expansion speed of the network structure; the self-repairing function of the anti-corrosion coating finally obtained is stronger, faster, and has better strength and toughness.

[0014] By adopting the above technical scheme, the reason for using rare earth phosphors is that the transition condition of rare earth elements is sunlight in nature, and this luminescence process can be completed in nature, so that after the anti-corrosion coating is scratched, the rare earth phosphors are exposed and irradiated by sunlight, and the rare earth elements therein transition from low energy levels to high energy levels. The outer electrons are unstable and are more likely to form complexes with strong ligand imidazole N-heterocyclic carbenes. The formed complexes have catalytic functions for the aldehyde condensation and other coupling reactions occurring in the self-healing gel material and the self-healing toughening material. When the anti-corrosion coating is scratched, the rapid response of the phosphor components accelerates the healing of the self-healing components, so that the healing time of the anti-corrosion coating is short and the healing ability is strong.

[0015] The purpose of coating the rare earth phosphor with nano-binder is to enable the phosphor component to be firmly adhered to the substrate through the nano-binder, so that the self-healing component can also be firmly adhered to the substrate, making it difficult for the anti-corrosion coating to crack and fall off.

[0016] Optionally, the rare earth element in the rare earth phosphor is Dy 3+ and Eu 3+ One or more of .

[0017] By adopting the above technical solution, Dy 3+ and Eu 3+ As the rare earth elements in rare earth phosphors, they are all trivalent rare earth elements, which can form complexes with strong binding force with imidazole N-heterocyclic carbenes. They have stable catalytic function on the aldol condensation and other coupling reactions occurring in self-healing gel materials and self-healing toughening materials, accelerate the healing of self-healing components, and make the anti-corrosion coating have short healing time and strong healing ability.

[0018] In a second aspect, the present application provides a method for preparing an anti-corrosion coating with a self-repairing function, and the specific method is as follows:

[0019] A method for preparing an anti-corrosion coating with a self-repairing function comprises the following steps: mixing and stirring the self-healing gel material, the self-healing toughening material and the imidazole N-heterocyclic carbene to obtain a self-healing component.

[0020] By adopting the above technical scheme, after the imidazole N-heterocyclic carbene is mixed with the self-healing gel material and the self-healing toughening material, the imidazole N-heterocyclic carbene can be interspersed between the self-healing gel material and the self-healing toughening material. When the imidazole N-heterocyclic carbene is combined with the rare earth element in the rare earth phosphor, the formed complex can act as a catalyst to uniformly catalyze the self-healing component inside the self-healing gel material and the self-healing toughening material, so that the self-healing ability of the self-healing component is stronger and the self-healing time is shorter.

[0021] Optionally, the preparation method of the self-healing component includes the following steps: Sal, mixing polyvinyl alcohol and 3-methyl-15-glutaraldehyde, adding methanol while stirring, then adding sodium bicarbonate, and continuing to stir to obtain a self-healing gel precursor; Sa2, mixing cellulose with N,N-dimethylformamide, then adding glutaraldehyde and sodium hydroxide, and continuing to stir to obtain a self-healing toughening material precursor; Sa3, mixing imidazole N-heterocyclic carbene, a self-healing gel precursor and a self-healing toughening material precursor, heating to volatilize methanol and N,N-dimethylformamide, and when the total volume of methanol and N,N-dimethylformamide is 40%-50% of the initial volume, a self-healing component is obtained;

[0022] The preparation method of the phosphor component comprises the following steps: Sb1, mixing rare earth phosphor and n-hexane, adding nano binder dropwise while stirring to obtain a phosphor component precursor; Sb2, heating the phosphor component precursor to remove the n-hexane, and obtaining the phosphor component when the total volume is 30%-40% of the initial volume.

[0023] By adopting the above technical scheme, the self-healing gel material precursor and the self-healing toughening material precursor are prepared respectively in step S1a and step Sa2. The purpose of separate preparation is to allow the self-healing gel material precursor to be better cross-linked so as to exert the maximum self-healing function of the self-healing gel material, and to allow the self-healing toughening material precursor to be better cross-linked so as to exert the better toughening and strengthening functions of the self-healing toughening material precursor; in step Sa3, the self-healing toughening material precursor and the self-healing gel material precursor are mixed, which can ensure that the self-healing toughening material precursor and the self-healing gel material precursor are combined with each other while their own performances remain stable, so that the self-healing anti-corrosion coating finally obtained has both self-healing function and toughening and strengthening function.

[0024] In step Sbl, the rare earth phosphor is mixed with n-hexane so that the rare earth phosphor can be uniformly dissolved in the n-hexane, and then the nano binder is added dropwise, and the nano binder is slowly coated on the surface of the rare earth phosphor to form nano binder-coated rare earth phosphor microspheres; after removing part of the n-hexane in step Sb2, the adhesion of the nano binder on the rare earth phosphor is stronger, and the phosphor component finally obtained can be firmly adhered to the substrate, and the self-healing component can also be firmly adhered to the substrate, and it is difficult for the anti-corrosion coating to crack and fall off.

[0025] Optionally, the method of using the anti-corrosion coating with self-repairing function is that a fluorescent powder component is coated on a substrate, and a self-healing component is coated on the fluorescent powder component.

[0026] By adopting the above technical scheme, the phosphor component is coated on the substrate, and the strong adhesion of the phosphor component enables the phosphor component to adhere firmly to the substrate; the self-healing component is coated on the phosphor component, so that after the self-healing component is scratched, the phosphor component is exposed, and after being irradiated by sunlight, the trivalent rare earth ions in the phosphor component undergo transition from the base layer to the excitation layer, and the stability is reduced. The trivalent rare earth ions are more likely to form a complex with the imidazole N-heterocyclic carbene, and this complex can act as a catalyst to catalyze the self-healing of the self-healing component, thereby shortening the self-healing time of the self-healing component.

[0027] In a third aspect, the present application provides an application of an anti-corrosion coating with a self-repairing function, and the specific application is as follows:

[0028] A self-healing anti-corrosion coating can be used in many fields such as construction, aerospace, transportation, electronics, sports and military supplies.

[0029] By adopting the above technical solutions, anti-corrosion coatings with self-repairing functions can be applied in multiple fields.

[0030] In summary, this application has the following beneficial effects:

[0031] 1. The catalyst in the self-healing anti-corrosion coating of the present application has the effect of accelerating the self-healing process of the self-healing component and shortening the self-healing time of the anti-corrosion coating, because when the anti-corrosion coating is damaged, the catalyst can respond instantly and automatically start the catalytic function. Therefore, the addition of the catalyst improves the self-healing function of the anti-corrosion coating with self-healing function;

[0032] 2. After the anti-corrosion coating in the present application is scratched, the rare earth phosphor is exposed and irradiated by sunlight, and the rare earth elements therein transition from a low energy level to a high energy level, and the outer electrons are unstable, making it easier to form a complex with the strong ligand imidazole N-heterocyclic carbene. The formed complex has a catalytic function for the aldol condensation and other coupling reactions occurring in the self-healing gel material and the self-healing toughening material. Therefore, the rare earth phosphor can complete this luminescence process in nature without the need for external conditions, thereby promoting the rapid self-healing speed of the anti-corrosion coating;

[0033] 3. In the present application, the imidazole N*heterocyclic carbene is in the form of a self-healing gel material and a self-healing toughening material. Since the imidazole N-heterocyclic carbene is coordinated with the rare earth elements in the rare earth phosphor, when the imidazole N-heterocyclic carbene can be interspersed between the self-healing gel material and the self-healing toughening material, the imidazole N-heterocyclic carbene forms a complex with the rare earth elements in the rare earth phosphor and acts as a catalyst to uniformly catalyze the self-healing component inside the self-healing component, thereby making the self-healing ability of the self-healing component stronger and the self-healing time shorter. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 It is the line graph of healing rate of different samples;

[0035] Figure 2 This is a Hitachi cold field emission electron microscope image of the self-healing component;

[0036] Figure 3 This is a Hitachi cold field emission electron microscope morphology photograph of the fractured sample prepared in Example 3;

[0037] Figure 4 This is a Hitachi cold field emission electron microscope morphology image of the sample prepared in Example 3, which was healed 12 hours after fracture. DETAILED DESCRIPTION

[0038] The raw materials of the embodiments and comparative examples of the present application can all be purchased commercially, and the rare earth phosphor is purchased from Hangzhou Jikang New Materials Co., Ltd.; the carbon quantum dots are carboxyl-modified carbon quantum dots, purchased from Suzhou Beike Nanotechnology Co., Ltd.; polyvinyl alcohol is purchased from Shandong Qiansheng Chemical Co., Ltd.; 3-formylglutaraldehyde is purchased from Qike New Materials Technology (Shanghai) Co., Ltd.; cellulose is microcrystalline cellulose 9004-34-6, purchased from Shandong Nengju Chemical Co., Ltd.; N,N-dimethylformamide is purchased from Jinan Qihang Chemical Technology Co., Ltd.; 1,3-bis(2,4,6-trimethylphenyl)imidazolium chloride, CAS173035-10-4, purchased from Hubei Biaoyue Biotechnology Development Co., Ltd.; nano-silica dispersion, CAS No. 14808-60-7, purchased from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.

[0039] The present application is further described in detail below in conjunction with embodiments and comparative examples.

[0040] Example 1

[0041] A method for preparing an anti-corrosion coating with a self-repairing function comprises the following steps:

[0042] The preparation method of the self-healing component comprises the following steps: Sal, 10g of polyvinyl alcohol and 20g of 3-methyl-15-glutaraldehyde are mixed and stirred at a speed of 500rpm and a temperature of 50°C for 30min, 40g of methanol is added while stirring, and then 5g of sodium bicarbonate is added, and stirring is continued for 5h to obtain a self-healing gel precursor; Sa2, 10g of cellulose and 45g of N, N-dimethylformamide are mixed and stirred at a speed of 800rpm and a temperature of 50°C for 40min, and then 20g of glutaraldehyde and 5g of sodium hydroxide are added, and stirring is continued for 5h to obtain a self-healing toughening material precursor; Sa3, 20g 1,3-bis(2,4,6-trimethylphenyl)imidazolium chloride, the self-healing gel precursor and the self-healing toughening material precursor prepared above are evaporated by a rotary evaporator at a speed of 100 rpm and a temperature of 68° C., and a self-healing component is obtained when the total volume of methanol and N,N-dimethylformamide is 50% of the initial volume;

[0043] The preparation method of the phosphor component comprises the following steps: Sbl, 20g of rare earth phosphor 4SrO.7Al 2 O 3 : Eu and 30g of n-hexane are mixed and stirred at room temperature at a speed of 800rpm, and 8g of nano-silicon dioxide dispersion is added dropwise while stirring, with a dropping speed of 1mL / 30min. After the addition is completed, stirring is continued for 24h to obtain a phosphor component precursor; Sb2, the phosphor component precursor is heated and volatilized by using a rotary evaporator at a speed of 100rpm and a temperature of 68°C to volatilize the n-hexane, and when the total volume is 40% of the initial volume, the phosphor component is obtained;

[0044] A method for using an anti-corrosion coating with a self-repairing function: grind a ferrous plate with 500-mesh sandpaper, clean the grinded surface with alcohol, and let it stand to dry; spray a fluorescent powder component on a waterproof cardboard substrate with a flat surface and the ferrous plate, respectively, with a spraying thickness of 0.5 mm, and spray a self-healing component on the fluorescent powder component, with a spraying thickness of 1.5 mm, to obtain samples of two anti-corrosion coatings with different substrates coated with a self-repairing function.

[0045] Example 2

[0046] A method for preparing an anti-corrosion coating with a self-repairing function comprises the following steps:

[0047] The preparation method of the self-healing component comprises the following steps: Sa1, 20g of polyvinyl alcohol and 15g of 3-methyl-15-glutaraldehyde are mixed and stirred at a speed of 500rpm and a temperature of 50°C for 30min, 20g of methanol is added while stirring, and then 8g of sodium bicarbonate is added, and stirring is continued for 5h to obtain a self-healing gel precursor; Sa2, 15g of cellulose and 20g of N,N-dimethylformamide are mixed and stirred at a speed of 800rpm and a temperature of 50°C for 40min, and then 10g of glutaraldehyde and 7g of sodium hydroxide are added, and stirring is continued for 5h to obtain a self-healing toughening material precursor; Sa3, 50g 1,3-bis(2,4,6-trimethylphenyl)imidazolium chloride, the self-healing gel precursor and the self-healing toughening material precursor prepared above are evaporated by a rotary evaporator at a speed of 100 rpm and a temperature of 68° C., and a self-healing component is obtained when the total volume of methanol and N,N-dimethylformamide is 50% of the initial volume;

[0048] The preparation method of the phosphor component comprises the following steps: Sb1, 30g of rare earth phosphor 4SrO.7AL 2 0 3 : Eu and 50g of n-hexane are mixed and stirred at room temperature at a speed of 800rpm, and 5g of nano-silicon dioxide dispersion is added dropwise while stirring, with a dropping speed of 1mL / 30min. After the addition is completed, stirring is continued for 24h to obtain a phosphor component precursor; Sb2, the phosphor component precursor is heated and volatilized by using a rotary evaporator at a speed of 100rpm and a temperature of 68°C to volatilize the n-hexane, and when the total volume is 40% of the initial volume, the phosphor component is obtained;

[0049] A method for using an anti-corrosion coating with a self-repairing function: grind a ferrous plate with 500-mesh sandpaper, clean the grinded surface with alcohol, and let it stand to dry; spray a fluorescent powder component on a waterproof cardboard substrate with a flat surface and the ferrous plate, respectively, with a spraying thickness of 0.5 mm, and spray a self-healing component on the fluorescent powder component, with a spraying thickness of 1.5 mm, to obtain samples of two anti-corrosion coatings coated with a self-repairing function on different substrates.

[0050] Example 3

[0051] A method for preparing an anti-corrosion coating with a self-repairing function comprises the following steps:

[0052] The preparation method of the self-healing component comprises the following steps: Sal, 15g of polyvinyl alcohol and 18g of 3-methyl-15-glutaraldehyde are mixed and stirred at a speed of 500rpm and a temperature of 50°C for 30min, 30g of methanol is added while stirring, and then 7g of sodium bicarbonate is added, and stirring is continued for 5h to obtain a self-healing gel precursor; Sa2, 12g of cellulose and 33g of N, N-dimethylformamide are mixed and stirred at a speed of 800rpm and a temperature of 50°C for 40min, and then 15g of glutaraldehyde and 6g of sodium hydroxide are added, and stirring is continued for 5h to obtain a self-healing toughening material precursor; Sa3, 35g 1,3-bis(2,4,6-trimethylphenyl)imidazolium chloride and the self-healing gel precursor and the self-healing toughening material precursor prepared above are evaporated by a rotary evaporator at a speed of 100 rpm and a temperature of 68° C., and a self-healing component is obtained when the total volume of methanol and N,N-dimethylformamide is 50% of the initial volume;

[0053] The preparation method of the phosphor component comprises the following steps: Sb1, 25g of rare earth phosphor 4SrO.7AL 2 0 3 : Eu and 40g n-hexane are added at a speed of 800rpm at a speed of 1mL / 30min. After the addition is completed, stirring is continued for 24h, mixed and stirred at room temperature, and 6.5g of nano-silicon dioxide dispersion is added dropwise while stirring to obtain a phosphor component precursor; Sb2, the phosphor component precursor is heated and volatilized by using a rotary evaporator at a speed of 100rpm and a temperature of 68°C to volatilize the n-hexane, and when the total volume is 40% of the initial volume, the phosphor component is obtained;

[0054] A method for using an anti-corrosion coating with a self-repairing function: grind a ferrous plate with 500-mesh sandpaper, clean the grinded surface with alcohol, and let it stand to dry; spray a fluorescent powder component on a waterproof cardboard substrate with a flat surface and the ferrous plate, respectively, with a spraying thickness of 0.5 mm, and spray a self-healing component on the fluorescent powder component, with a spraying thickness of 1.5 mm, to obtain samples of two anti-corrosion coatings coated with a self-repairing function on different substrates.

[0055] Example 4

[0056] The difference from Example 3 is that the phosphor in step Sb1 is replaced by carbon quantum dots of equal weight.

[0057] Example 5

[0058] The difference from Example 3 is that in step Sa1, 3-methyl-15-glutaraldehyde is not added.

[0059] Example 6

[0060] The difference from Example 3 is that in step Sa2, glutaraldehyde is not added.

[0061] Example 7

[0062] The difference from Example 3 is that in step Sb1, no nano-silicon dioxide dispersion is added.

[0063] Comparative Example 1

[0064] The difference from Example 3 is that the preparation method of the self-healing component does not include step Sa1, and the specific method is as follows:

[0065] A method for preparing an anti-corrosion coating with a self-repairing function comprises the following steps:

[0066] The preparation method of the self-healing component comprises the following steps: 12g of cellulose and 33g of N,N-dimethylformamide are mixed and stirred at a speed of 800rpm and a temperature of 50°C for 40min, then 15g of glutaraldehyde and 6g of sodium hydroxide are added, and stirring is continued for 5h to obtain a self-healing toughening material precursor; 35g of 1,3-bis(2,4,6-trimethylphenyl)imidazolium chloride and the self-healing toughening material precursor prepared above are volatilized by using a rotary evaporator at a speed of 100rpm and a temperature of 68°C, and the self-healing component is obtained when the total volume of N,N-dimethylformamide is 50% of the initial volume;

[0067] The preparation method of the phosphor component comprises the following steps: Sb1, 25g of rare earth phosphor 4SrO.7AL 2 0 3 : Eu and 40g of n-hexane are mixed and stirred at room temperature at a speed of 800rpm, and 6.5g of nano-silicon dioxide dispersion is added dropwise while stirring, and the dropping speed is 1mL / 30min. After the addition is completed, stirring is continued for 24h to obtain a phosphor component precursor; Sb2, the phosphor component precursor is heated and volatilized by using a rotary evaporator at a speed of 100rpm and a temperature of 68°C to volatilize the n-hexane, and when the total volume is 40% of the initial volume, the phosphor component is obtained;

[0068] A method for using an anti-corrosion coating with a self-repairing function: grind a ferrous plate with 500-mesh sandpaper, clean the grinded surface with alcohol, and let it stand to dry; spray a fluorescent powder component on a waterproof cardboard substrate with a flat surface and the ferrous plate, respectively, with a spraying thickness of 0.5 mm, and spray a self-healing component on the fluorescent powder component, with a spraying thickness of 1.5 mm, to obtain samples of two different substrates coated with anti-corrosion coatings with a self-repairing function.

[0069] Comparative Example 2

[0070] The difference from Example 3 is that the Sa2 step is not performed in the preparation method of the self-healing component. The specific method is as follows:

[0071] A method for preparing an anti-corrosion coating with a self-repairing function comprises the following steps:

[0072] The preparation method of the self-healing component comprises the following steps: mixing 15g of polyvinyl alcohol and 18g of 3-methyl-15-glutaraldehyde at a speed of 500rpm and a temperature of 50°C for 30min, adding 30g of methanol while stirring, and then adding 7g of sodium bicarbonate, and continuing to stir for 5h to obtain a self-healing gel precursor; using a rotary evaporator to volatilize methanol from 35g of 1,3-bis(2,4,6-trimethylphenyl)imidazolium chloride and the self-healing gel precursor prepared above at a speed of 100rpm and a temperature of 68°C, and when the total volume of methanol is 50% of the initial volume, a self-healing component is obtained;

[0073] The preparation method of the phosphor component comprises the following steps: Sb1, 25g of rare earth phosphor 4SrO.7AL 2 0 3 : Eu and 40g of n-hexane are mixed and stirred at room temperature at a speed of 800rpm, and 6.5g of nano-silicon dioxide dispersion is added dropwise while stirring, and the dropping speed is 1mL / 30min. After the addition is completed, stirring is continued for 24h to obtain a phosphor component precursor; Sb2, the phosphor component precursor is heated and volatilized by using a rotary evaporator at a speed of 100rpm and a temperature of 68°C to volatilize the n-hexane, and when the total volume is 40% of the initial volume, the phosphor component is obtained;

[0074] A method for using an anti-corrosion coating with a self-repairing function: grind a ferrous plate with 500-mesh sandpaper, clean the grinded surface with alcohol, and let it stand to dry; spray a fluorescent powder component on a waterproof cardboard substrate with a flat surface and the ferrous plate, respectively, with a spraying thickness of 0.5 mm, and spray a self-healing component on the fluorescent powder component, with a spraying thickness of 1.5 mm, to obtain samples of two anti-corrosion coatings coated with a self-repairing function on different substrates.

[0075] Comparative Example 3

[0076] The difference from Example 3 is that the anti-corrosion coating with self-repairing function does not contain a fluorescent powder component. The specific steps are as follows:

[0077] A method for preparing an anti-corrosion coating with a self-repairing function comprises the following steps:

[0078] The preparation method of the self-healing component comprises the following steps: Sa1, mixing 15g of polyvinyl alcohol and 18g of 3-methyl-15-glutaraldehyde at a speed of 500rpm and a temperature of 50°C for 30min, adding 30g of methanol while stirring, then adding 7g of sodium bicarbonate, and continuing to stir for 5h to obtain a self-healing gel precursor; Sa2, mixing 12g of cellulose and 33g of N,N-dimethylformamide at a speed of 800rpm and a temperature of 50°C for 40min, then adding 15g of glutaraldehyde and 6g of sodium hydroxide, and continuing to stir for 5h to obtain a self-healing toughening material precursor; Sa3, mixing 35g of 1,3-bis(2,4,6-trimethylphenyl)imidazolium chloride, the self-healing gel precursor and the self-healing toughening material precursor prepared above are evaporated by a rotary evaporator at a speed of 100 rpm and a temperature of 68°C to obtain a self-healing component when the total volume of methanol and N,N-dimethylformamide is 50% of the initial volume;

[0079] A method for using an anti-corrosion coating with a self-repairing function: grind a ferrous plate with 500-mesh sandpaper, clean the grinded surface with alcohol, and let it stand to dry; spray a self-healing component on a waterproof cardboard substrate with a flat surface and the ferrous plate, respectively, with a spraying thickness of 1.5 mm, to obtain samples of two anti-corrosion coatings coated with a self-repairing function on different substrates.

[0080] Comparative Example 4

[0081] The difference from Example 3 is that 1,3-bis(2,4,6-trimethylphenyl)imidazolium chloride is not added in step Sa3, and the specific steps are as follows:

[0082] A method for preparing an anti-corrosion coating with a self-repairing function comprises the following steps:

[0083] The preparation method of the self-healing component comprises the following steps: Sa1, mixing 15g of polyvinyl alcohol and 18g of 3-methyl-15-glutaraldehyde at a speed of 500rpm and a temperature of 50°C for 30min, adding 30g of methanol while stirring, then adding 7g of sodium bicarbonate, and continuing to stir for 5h to obtain a self-healing gel precursor; Sa2, mixing 12g of cellulose and 33g of N,N-dimethylformamide at a speed of 800rpm and a temperature of 50°C for 40min, then adding 15g of glutaraldehyde and 6g of sodium hydroxide, and continuing to stir for 5h to obtain a self-healing toughening material precursor; Sa3, using a rotary evaporator to volatilize methanol and N,N-dimethylformamide from the self-healing gel precursor and the self-healing toughening material precursor prepared above at a speed of 100rpm and a temperature of 68°C, and when the total volume of methanol and N,N-dimethylformamide is 50% of the initial volume, a self-healing component is obtained;

[0084] The preparation method of the phosphor component comprises the following steps: Sb1, 25g of rare earth phosphor 4SrO.7AL 2 0 3 : Eu and 40g of n-hexane are mixed and stirred at room temperature at a speed of 800rpm, and 6.5g of nano-silicon dioxide dispersion is added dropwise while stirring, with a dropping speed of 1mL / 30min. After the addition is completed, stirring is continued for 24h to obtain a phosphor component precursor; Sb2, the phosphor component precursor is heated at a speed of 100rpm and a temperature of 68°C using a rotary evaporator to volatilize the n-hexane, and when the total volume is 40% of the initial volume, the phosphor component is obtained;

[0085] A method for using an anti-corrosion coating with a self-repairing function: grind a ferrous plate with 500-mesh sandpaper, clean the grinded surface with alcohol, and let it stand to dry; spray a fluorescent powder component on a waterproof cardboard substrate with a flat surface and the ferrous plate, respectively, with a spraying thickness of 0.5 mm, and spray a self-healing component on the fluorescent powder component, with a spraying thickness of 1.5 mm, to obtain samples of two anti-corrosion coatings coated with a self-repairing function on different substrates.

[0086] Comparative Example 5

[0087] The difference from Example 3 is that step Sa1, step Sa2 and step Sa3 are performed simultaneously. The specific steps are as follows:

[0088] A method for preparing an anti-corrosion coating with a self-repairing function comprises the following steps:

[0089] The preparation method of the self-healing component comprises the following steps: 15g of polyvinyl alcohol, 18g of 3*methyl*15-glutaraldehyde, 2g of cellulose and 15g of glutaraldehyde are mixed and stirred at a speed of 500rpm and a temperature of 50°C for 40min, 30g of methanol and 33g of N,N-dimethylformamide are added while stirring, and then 7g of sodium bicarbonate and 6g of sodium hydroxide are added, stirring is continued for 5h, and finally 35g of 1,3-bis(2,4,6-trimethylphenyl)imidazolium chloride is added, and methanol and N,N-dimethylformamide are volatilized by a rotary evaporator at a speed of 100rpm and a temperature of 68°C, and a self-healing component is obtained when the total volume of methanol and N,N-dimethylformamide is 50% of the initial volume;

[0090] The preparation method of the phosphor component comprises the following steps: Sb1, 25g of rare earth phosphor 4SrO.7AL 2 0 3: Eu and 40g of n-hexane are mixed and stirred at room temperature at a speed of 800rpm, and 6.5g of nano-silicon dioxide dispersion is added dropwise while stirring, with a dropping speed of 1mL / 30min. After the addition is completed, stirring is continued for 24h to obtain a phosphor component precursor; Sb2, the phosphor component precursor is heated at a speed of 100rpm and a temperature of 68°C using a rotary evaporator to volatilize the n-hexane, and when the total volume is 40% of the initial volume, the phosphor component is obtained;

[0091] A method for using an anti-corrosion coating with a self-repairing function: grind a ferrous plate with 500-mesh sandpaper, clean the grinded surface with alcohol, and let it stand to dry; spray the fluorescent powder components on a waterproof cardboard substrate with a flat surface and the ferrous plate with a spraying thickness of 0.5 mm, and spray the self-healing component on the fluorescent powder component with a spraying thickness of 1.5 mm, to obtain samples of two anti-corrosion coatings with different substrates coated with a self-repairing function.

[0092] Comparative Example 6

[0093] Use commercially available self-healing anti-corrosion coating, brand: Fenyangtang; type: heavy anti-corrosion coating; model: vinyl ester coating.

[0094] Performance testing

[0095] Detection Methods

[0096] Adhesion test method: Use QFZ-2 coating adhesion tester to test adhesion according to national standard GB / T1720; Pencil hardness: Use QHQ-A pencil scratch hardness tester to test according to national standard GB / T6739, use pencils of different hardness to scratch the coating until the coating is damaged, determine the hardness of the coating, and select samples sprayed on the iron plate. The data are recorded in Table 1.

[0097] Self-healing rate detection method: Each sample was cut and then connected. After different healing times, the self-healing rates of the samples at different times were tested, which were the fracture strength recovery rate after 12h, the fracture strength after 24h, the fracture strength recovery rate after 36h, and the fracture strength recovery rate after 48h. The fracture strength recovery rate R(α) = α healed / α initial The samples selected are those sprayed on waterproof paperboard, and the data are recorded in the appendix of the instruction manual. Figure 1 middle.

[0098] The self-healing component prepared in Example 3 was photographed by Hitachi cold field emission electron microscope and recorded in the appendix of the manual. Figure 2 In Example 3, the sample was prepared after the sample was broken and healed for 12 hours. The sample was sprayed on the waterproof cardboard and recorded in the appendix of the manual. Figure 3and Figure 4 middle.

[0099] Table 1 Performance test results of Examples 1-7 and Comparative Examples 1-6

[0100] Adhesion hardness Example 1 4H 5 Example 2 4H 5 Example 3 5H 6 Example 4 5H 6 Example 5 4H 5 Example 6 2H 5 Example 7 3H 3 Comparative Example 1 4H 5 Comparative Example 2 2H 5 Comparative Example 3 3H 3 Comparative Example 4 3H 4 Comparative Example 5 4H 6 Comparative Example 6 4H 5

[0101] Combined with the data of Examples 1, 2, and 3 and the appendix of the specification Figure 1 It can be seen that the only difference between Examples 1, 2, and 3 is the different raw material composition ratios. The anti-corrosion coating prepared in Example 3 has the strongest adhesion on the iron plate, the largest pencil hardness, and a 12h fracture strength recovery rate that is higher than that of Examples 1 and 2, proving that the anti-corrosion coating prepared in Example 3 has a stronger healing ability after 12h, and the raw material ratio of Example 3 is the best raw material ratio.

[0102] Combine the data of Example 3 and Example 4 with the attached manual Figure 1 It can be seen that Example 4 replaces the rare earth phosphor in Example 3 with an equal weight of carbon quantum dots. Although the adhesion and pencil hardness of the anti-corrosion coating prepared in Example 4 on the iron plate are the same as those of the anti-corrosion coating prepared in Example 3, the fracture strength recovery rate of the anti-corrosion coating prepared in Example 4 is lower than that of Example 3 after 12 hours, and after 24 hours, 36 hours and 48 hours, the fracture strength recovery rate of the anti-corrosion coating prepared in Example 4 is lower than that of Example 3, which proves that carbon quantum dots cannot replace rare earth phosphors because there are no rare earth elements in carbon quantum dots.

[0103] Combine the data of Examples 5 and 6 with those of Example 3 and the attached manual. Figure 1 It can be seen that compared with Example 3, 3-methyl-15-glutaraldehyde and glutaraldehyde were not added in Examples 5 and 6 respectively, and the adhesion of the anti-corrosion coatings prepared in Examples 5 and 6 on the iron plate was reduced, and the pencil hardness was reduced to 2H, which proved that 3-methyl-15-glutaraldehyde and glutaraldehyde were raw materials that must be added, and the reaction of glutaraldehyde with cellulose would indeed greatly increase the hardness of the anti-corrosion coating.

[0104] Combine the data of Example 7 and Example 3 with the attached Figure 1 It can be seen that compared with Example 3, no nano-adhesive was added to the phosphor component of Example 7. The adhesion of the anti-corrosion coating prepared in Example 7 on the iron plate was reduced to 3, and the pencil hardness was also reduced, which proved that the nano-adhesive was very important for the adhesion of the anti-corrosion coating.

[0105] Combine the data of Comparative Examples 1, 2 and Example 3 with the data of the appendix of the specification. Figure 1It can be seen that compared with Example 3, Comparative Examples 1 and 2 did not add self-healing gel precursor and self-healing toughening material precursor respectively. The adhesion and hardness of the anti-corrosion coatings prepared in Comparative Examples 1 and 2 on the horse iron plate were reduced, and the 12h fracture strength recovery rate was reduced to 31% and 34%, respectively. This proves that the self-healing gel precursor and the self-healing toughening material precursor are both very important to the self-healing ability of the anti-corrosion coating, and neither of them is dispensable.

[0106] Combined with the data of Comparative Examples 3, 4 and Example 3, the following Figure 1 It can be seen that compared with Example 3, Comparative Examples 3 and 4 do not add fluorescent powder components and imidazole N-heterocyclic carbene respectively. The adhesion and pencil hardness of the anti-corrosion coatings prepared in Comparative Examples 3 and 4 on the iron plate are greatly reduced, and the 12h breaking strength recovery rate is also reduced by about 15% to 21%, which proves that the fluorescent powder component and imidazole N-heterocyclic carbene are extremely important for the self-healing ability of the anti-corrosion coating, and neither of them can be missing.

[0107] The data sheet of Comparative Example 5 and Example 3 is attached. Figure 1 It can be seen that compared with Example 3, the raw materials for preparing the self-healing gel precursor, the self-healing toughening material precursor and the phosphor component in Example 5 are all reacted together, and the various properties of the anti-corrosion coating prepared are worse than those in Example 3, which proves that the preparation method of the present application is also extremely important.

[0108] Combining Comparative Example 6 with Example 3, it can be seen that Comparative Example 6 uses a commercially available self-healing coating, and its performance is inferior to that of the anti-corrosion coating prepared in Example 3.

[0109] Instructions attached Figure 2 It can be seen that the self-healing component prepared in Example 3 is indeed a mesh structure; Figure 3 The sample prepared in Example 3 is broken, and the instruction manual is attached. Figure 4 The sample prepared in Example 3 healed for 12 hours. It is obvious that the healing condition of the sample is better after 12 hours.

[0110] The embodiments are merely explanations of the present application and are not limitations of the present application. After reading this specification, those skilled in the art may make modifications to the embodiments without any creative contribution as needed. However, as long as they are within the scope of the claims of the present application, they are protected by the patent law.

Claims

1. An anti-corrosion coating with self-repairing function, characterized in that: It comprises a phosphor component and a self-healing component; the phosphor component comprises the following raw materials in parts by weight: 20-30 parts of rare earth phosphor, 5-8 parts of nano adhesive and 30-50 parts of n-hexane, and the nano adhesive coats the rare earth phosphor; the self-healing component comprises the following raw materials in parts by weight: 20-50 parts of imidazole N-heterocyclic carbene, 50-90 parts of self-healing gel and 40-90 parts of self-healing toughening material; Taking the self-healing gel as a reference, the self-healing gel comprises the following raw materials in parts by weight: 10-20 parts of polyvinyl alcohol, 15-20 parts of 3-methyl-1,5-glutaraldehyde, 5-8 parts of sodium bicarbonate and 20-40 parts of methanol; Taking the self-healing toughening material as a reference, the self-healing toughening material comprises the following raw materials in parts by weight: 10-15 parts of cellulose, 10-20 parts of glutaraldehyde, 4-7 parts of sodium hydroxide and 20-45 parts of N,N-dimethylformamide; The nano binder is a nano silicon dioxide dispersion; The rare earth element in the rare earth phosphor is Dy 3+ and Eu 3+ One or more of; The imidazole N-heterocyclic carbene is 1,3-bis(2,4,6-trimethylphenyl)imidazolium chloride; The preparation method of the self-healing component specifically comprises the following steps: Sa1, mixing polyvinyl alcohol and 3-methyl-1,5-glutaraldehyde, adding methanol while stirring, then adding sodium bicarbonate, and continuing to stir to obtain a self-healing gel precursor; Sa2, mixing cellulose and N,N-dimethylformamide, then adding glutaraldehyde and sodium hydroxide, and continuing to stir to obtain a self-healing toughening material precursor; Sa3, mixing imidazole N-heterocyclic carbene, a self-healing gel precursor and a self-healing toughening material precursor, heating and volatilizing methanol and N,N-dimethylformamide, and when the total volume of methanol and N,N-dimethylformamide is 40%-50% of the initial volume, a self-healing component is obtained; The preparation method of the phosphor component specifically includes the following steps: Sb1, mixing and stirring the rare earth fluorescent component and n-hexane, and adding a nano binder dropwise while stirring to obtain a phosphor component precursor; Sb2, heating the phosphor component precursor to remove the n-hexane, and obtaining the phosphor component when the total volume is 30%-40% of the initial volume.

2. The method for using the anti-corrosion coating with self-repairing function according to claim 1, characterized in that: The phosphor component is coated on a substrate, and the self-healing component is coated on the phosphor component.